2017
DOI: 10.3390/brainsci7040035
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Mental Spelling Application Based on Eye Tracking and SSVEP-Based BCI

Abstract: Steady state visual evoked potentials (SSVEPs)-based Brain-Computer interfaces (BCIs), as well as eyetracking devices, provide a pathway for re-establishing communication for people with severe disabilities. We fused these control techniques into a novel eyetracking/SSVEP hybrid system, which utilizes eye tracking for initial rough selection and the SSVEP technology for fine target activation. Based on our previous studies, only four stimuli were used for the SSVEP aspect, granting sufficient control for most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…In a 30-target speller [8], a webcam-based eye tracking method was only able to detect binary gaze direction (left vs right). Another hybrid BCI obtained an information transfer rate (ITR) similar to SSVEP, but much lower than eye tracking [9]. According to high performance reported for eye tracking and SSVEP BCI [3], [5], the hybrid method is expected to achieve much higher performance than the existing systems.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a 30-target speller [8], a webcam-based eye tracking method was only able to detect binary gaze direction (left vs right). Another hybrid BCI obtained an information transfer rate (ITR) similar to SSVEP, but much lower than eye tracking [9]. According to high performance reported for eye tracking and SSVEP BCI [3], [5], the hybrid method is expected to achieve much higher performance than the existing systems.…”
Section: Introductionmentioning
confidence: 96%
“…Several recent studies have combined SSVEP and eye tracking to develop hybrid BCIs for spelling [8], [9]. However, due to performance gap between the two modalities, the hybrid systems did not achieve large performance improvement.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that an SSVEP-based BCI performed better than an eye tracking-based speller when targets are densely located and small in size. Recently, eye tracking has been combined with EEG to remove ocular artifacts from EEG signals [74,75] and to develop hybrid BCI systems [65,[76][77][78][79][80][81]. All these studies have shown improved performance as compared to EEG only, as well as the feasibility of combining EEG with eye tracking.…”
Section: Introductionmentioning
confidence: 99%
“…EEG-based BCI has several paradigms for signal acquisition such as motor imagery (MI) [6]- [8], event-related potential (ERP) [9], [10], and movement-related cortical potential (MRCP) [2], [11]. As applications of EEGbased BCI, a robotic arm [6], [12], [13], a speller [4], [14]- [16], a wheelchair [17], and a drone [18]- [21] were commonly used for communication between human and machines. Recently, a BCI-based drone swarm is one of the most interesting topics ( Fig.…”
Section: Introductionmentioning
confidence: 99%